2017
DOI: 10.1161/circresaha.116.310058
|View full text |Cite
|
Sign up to set email alerts
|

Cardiomyocyte Proliferation

Abstract: The inability of the adult heart to repair or regenerate is manifested in prevalent morbidity and mortality related to myocardial infarction and heart failure. Cardiomyocyte proliferation, especially after myocardial infarction or in the context of heart failure, has been an area of intense research by many investigators for decades. As a researcher working in this area for the past 25 years, this has been an exciting time, requiring an open mind in leaving old accepted ideas behind and moving forward towards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…T-cell receptor-mediated signaling alone is adequate to induce Treg differentiation in neonates without the need of IL-2 and TGF-β that are both required for adult Treg differentiation 39 . Therefore, in addition to the binuclear feature of adult cardiomyocytes that exit the cell cycle irreversibly 40 , the more effective Th1 and Th17 responses and less effective Treg responses of the adult mice could partly explain that the adult heart is less amenable for repair compared to the neonates. Given the developmental differences in various immune cell types including CD4 + T-cells, CD8 + T-cells and macrophages, ablation of CD4 + T-cells alone was insufficient to promote adult heart repair.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell receptor-mediated signaling alone is adequate to induce Treg differentiation in neonates without the need of IL-2 and TGF-β that are both required for adult Treg differentiation 39 . Therefore, in addition to the binuclear feature of adult cardiomyocytes that exit the cell cycle irreversibly 40 , the more effective Th1 and Th17 responses and less effective Treg responses of the adult mice could partly explain that the adult heart is less amenable for repair compared to the neonates. Given the developmental differences in various immune cell types including CD4 + T-cells, CD8 + T-cells and macrophages, ablation of CD4 + T-cells alone was insufficient to promote adult heart repair.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, cardiomyocytes were thought to have largely limited proliferative ability due to their terminal differentiation. 5 The cardiomyocytes of neonatal mouse hearts display remarkable regenerative ability [6][7][8][9] ; however, this ability is quickly lost seven days after birth. 10 After this transitionary stage, the adult cardiomyocytes display limited proliferative ability after injury, a mechanism proposed to also occur in humans.…”
Section: Impact Statementmentioning
confidence: 99%
“…With a final concentration of cells in the bioinks was 300 million cells mL −1 , the total number of cells for constructing such a model is ≈15 million. Recently, some studies showed the possibilities of boosting the proliferation of adult CMs by removing the cell cycle blockers and/or adding drugs . With the turnover rate of CMs improved, the fabrication of large size cardiac muscle tissues, even whole heart, would be made possible.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Recently, some studies showed the possibilities of boosting the proliferation of adult CMs by removing the cell cycle blockers and/or adding drugs. [92][93][94] With the turnover rate of CMs improved, the fabrication of large size cardiac muscle tissues, even whole heart, would be made possible. Finally, the specific requirement of smooth muscle tissue engineering is the heterogeneous distribution of SMCs with their neighboring cells, e.g., ECs, instead of a simple mixing of all types of cells.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%